Catalytic epoxidation using dioxidomolybdenum(VI) complexes with tridentate aminoalcohol phenol ligands - Hossain Md. Kamal; Schachner Jörg A.; Haukka Matti; Mösch-Zanetti Nada C.; Nordlander Ebbe; Lehtonen Ari (ELSEVIER SCIENCE SA, 2022)
Reaction of the tridentate aminoalcohol phenol ligands 2,4-di-tert-butyl-6-(((2 hydroxyethyl)(methyl)amino)methyl)phenol (H2L1) and 2,4-di-tert-butyl-6-(((1-hydroxybutan-2-yl)amino)methyl)phenol (H2L2) with [MoO2(acac)(2)] in methanol solutions resulted in the formation of [MoO2(L-1)(MeOH)] (1) and [MoO2(L-2)(MeOH)] (3), respectively. In contrast, the analogous reactions in acetonitrile afforded the dinuclear complexes [Mo2O2(mu-O)(2)(L-1)(2)] (2) and [Mo2O2(mu-O)(2)(L-2)(2)] (4). The corresponding reactions with the potentially tetradentate ligand 3-((3,5-di-tert-butyl-2-hydroxybenzyl)(methyl)amino)propane-1,2-diol (H3L3) led to the formation of the mononuclear complex [MoO2(L-3)(MeOH)] (5) in methanol while in acetonitrile solution a trinuclear structure [Mo3O3(mu-O)(3)(L-3)(3)] (6) was obtained. In both cases, the ligand moiety L-3 coordinated in a tridentate fashion. The catalytic activities of complexes 1-6 in epoxidation of five different olefins, S1-5, with tert-butyl hydroperoxide and hydrogen peroxide were studied. The catalytic activities were found to be moderate to good for the reaction of substrate cis-cyclooctene S1, while all complexes were less active in the epoxidation of the more challenging substrates S2-5. The molecular structures of 1, 2, 4 and 6 were determined by single crystal X-ray diffraction analyses.